POLICY DIRECTIONS AND AUTHORITIES OF REGENCY/CITY GOVERNMENTS IN THE MARINE AND FISHERIES SECTOR WITH THE EFFECT OF LAW NUMBER 23 OF 2014 - Ahmad Duroni Nasution (Proceeding International Seminar of Islamic Studies, 2023)
Since the enactment of Law Number 23 of 2014 concerning Regional Government, there have been very significant different provisions in determining policies in each region, especially in the maritime and fisheries sector. In the previous regional government regulations, namely Law Number 32 of 2004, regional governments were given the broadest authority to manage resources in marine areas, but since the latest regulations, the maritime and fisheries section is included in concurrent government affairs which must be coordinated between the central government. , provincial government and district/city government. Therefore, it is necessary to further examine the limitations and direction of policy and authority that can be exercised by district/city regional governments in the maritime and fisheries sectors since the enactment of Law Number 23 of 2014 concerning Regional Government. The aim of this research is to discover the legal relationship between the central government and regional governments in the marine and fisheries sector, to discover concurrent government affairs between the central government and provincial and district/city regions in the marine and fisheries sector, and to discover the position of district/city governments in Law Number 23 of 2014 in determining policy direction in the marine and fisheries sector. This type of research is normative juridical, while the nature of this research is prescriptive. The data source used is secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Document study data collection techniques, as well as using qualitative analysis. Based on the research results, it is known that the legal relationship between the central government and regional governments in the maritime and fisheries sector is part of concurrent government affairs, apart from that, concurrent government affairs are not mandatory government affairs but rather optional government affairs. Then it is understood that concurrent government affairs between the central government and provincial and district/city areas in the marine and fisheries sector as a whole are the authority and responsibility of the central government to make policies in the management of marine and national strategic space, as well as provincial regional governments being given the authority to manage natural resources in the sea in the region. Meanwhile, district/city governments are limited to supervising and empowering small fishermen and fish cultivation in district/city areas. Finally, it is known that the position of district/city governments in Law Number 23 of 2014 in determining policy direction in the marine and fisheries sector is limited to the empowerment of small fishermen and empowerment of fish cultivation businesses.